Association of Sleep Quality and Waking Time with Prediabetes: The Qazvin Metabolic Diseases Study, Iran. (16th August 2015) - Ghorbani, Azam; Esmailzadehha, Neda; Mohammadpoorasl, Asghar; Ziaee, Amir
Abstract : Aims . It is known that sleep has a major role in the regulation of endocrine functions and glucose metabolism. However, it is not clear whether the sleep pattern is affected at or prior to the onset of diabetes, among those with prediabetes. The purpose of this study was to determine the association of sleep patterns and prediabetes in Qazvin, Iran. Methods . A representative sample of residents of Qazvin was selected by multistage cluster random sampling method in 2011. Plasma glucose level and sleep quality were measured cross-sectionally as well as demographic characteristics. A logistic regression analysis was used to examine the association of sleep status and prediabetes. Results . Mean age was 39.3 ± 10.1 years. Of 958, 474 (49.47%) were female. Poor sleep quality was associated with 2.197-fold increased risk of prediabetes after adjustment for age, gender, body mass index, and metabolic syndrome. Conclusion . This study provides evidences that subjects with poor sleep quality are more likely to develop prediabetes than people with good sleep quality.